PENGARUH IMPLEMENTASI PEMASARAN RELASIONAL TERHADAP LOYALITAS PELANGGAN BNI BIRO REKTOR USU MEDAN (STUDI KASUS PADA MAHASISWA MANAJEMEN EKONOMI UNIVERSITAS SUMATERA UTARA) - Citrawisari Limanaga; Fivi Rahmatus Sofiyah (Universitas Sumatera Utara, 2013)
Abstract The purpose of this study is to know and to analyze the effect of the implementation of relationship marketing on customer loyalty in BNI Biro Rektor USU Medan with subjects management students of Economy Faculty of University of Sumatera Utara. Data used in this study is primary data and secondary data. Primary data was obtained from questionnaire. Secondary data was obtained from documentary studies of literature, journals, magazines, and web page relevan to the study. Data analyze method used in this study is multiple regression analyze method. Population in this study is all management students of Economy Faculty of University of Sumatera Utara year 2008-2010, who are customer of BNI Biro Rektor USU Medan, with total 517 people. Using Slovin’s formula, total sample used in this study is rounded up to 85 people. Sampling method used is accidental sampling. The result of this study is that the implementation of relationship marketing which consists of financial benefit, social benefit, and structural ties partially, except structural ties, has a positive influence on customer loyalty in BNI Biro Rektor USU Medan with subjects management students of Economy Faculty of University of Sumatera Utara. Keywords : Relationship Marketing, Customer Loyalty